DdPCR strategy to detect a gene-edited plant carrying a single variation point: Technical feasibility and interpretation issues. (July 2022) - Fraiture, Marie-Alice; Guiderdoni, Emmanuel; Meunier, Anne-Cécile; Papazova, Nina; Roosens, Nancy H.C.
Abstract: Gene-edited organisms and derived food and feed products commercialized on the European market falls within the scope of the Directive, 2001/18/EC. Therefore, the possibility to specifically detect and quantify them has become a priority. To this end, PCR-based approaches, such as real-time PCR and digital droplet PCR, targeting a single variation point carried by a gene-edited organism are expected to be suitable, even if potentially challenging at the technical level. However, additional issues related to the interpretation of the results can also be encountered. Indeed, given its possible spread, natural or through breeding programs, the presence of this single variation does not automatically prove the presence of the gene-edited organism. To overcome such critical issue, we proposed a general workflow to develop and validate a PCR-based method specific to a gene-edited organism in targeting its single variation point. First, based on in silico analyses, the possibility to technically design the PCR-based method as well as to discriminate the gene-edited organism using it single variation point are assessed. In case such parameters are confirmed, the performance of the developed PCR-based method are then tested in agreement with the minimum performance requirements for GMO testing. The use of the proposed general workflow was successfully illustrated through the development a 2-plex digital droplet PCR method targeting specifically a gene-edited rice carrying a single nucleotide insertion. The proposed workflow was thus considered as a key tool to support the competent authorities regarding the food and feed traceability. Highlights: A workflow to develop a PCR-method specific to a gene-edited organism is proposed. First, the possibility to technically design the method is investigated. Second, the method performance (specificity, sensitivity, applicability) is tested. Thereby, a ddPCR method specific to a gene-edited rice was successfully developed. Issues to unambiguously discriminate a gene-edited organism are also discussed.